Effects of different types of strings gauge in electric guitar playing / Hariz Zayyani Hamzah - Hamzah, Hariz Zayyani (Faculty of Music, 2015)
This study is conducted to investigate students understanding and awareness about the effects of different types of strings gauge in guitar playing. It is also included their approaches towards guitar techniques. This research also aims the student’s knowledge about the effects of strings gauge in guitar playing by giving the definition Although, this research also identified the problem faced by undergraduate students from Faculty of Music in UiTM when choosing various types of string in their playing‘ The causes and factors could be found when students overcome the problems are also identified in this research.